A Holocene Perspective of Vegetation Controls on Seasonal Boreal Wildfire Sizes Using Numerical Paleo-Ecology - Hély, Christelle; Chaste, Emeline; Girardin, Martin P.; Remy, Cécile C.; Blarquez, Olivier; Bergeron, Yves; Ali, Adam A. (Frontiers in Forests and Global Change, 2020)
Wildland fire is the most important disturbance in boreal forests of eastern North America, shaping composition, structure and spatial arrangement of the flora. Although the long-term evolution of frequency and quantity of biomass burnt in these forest are known relatively well from paleoecological studies, we know little about the evolution of fire sizes. Here, we developed a modelling framework that provides insights into processes and changes involved through time in the historical fire-vegetation-climate environment of the coniferous and mixedwood forests of eastern boreal North America, with a particular attention on the metric of fire size. On the one hand, lacustrine charcoal particles sequestered in sediments from mixedwood forest and coniferous forest regions (MF and CF, respectively) were analyzed with the most advanced statistical treatments to reconstruct changes in biomass burning, fire frequency, and their ratio, the fire size (FS index), over the last 7000 BP. On the other hand, a fire propagation model was used to simulate fire sizes in the past using both a reference landscape, whose MF and CF compositions through time were prescribed using pollen reconstructions, and climate inputs provided by the HadCM3BL-M1 snapshot simulations. Lacustrine charcoals showed that Holocene FS indices have not differed significantly between MF and CF due to high variability in fire frequencies. However, biomass burning from MF has always been lower than from CF, such differences being significant since 5000 BP. Beyond the variability, MF’s mean FS index was lower than CF’s one throughout the Holocene, with slight changes in both forests from 7000 to 1000 BP, and simultaneous increases over the last millennium. The fire model showed that MF fires were systematically smaller than CF ones throughout the Holocene, with larger differences in the past than today. The fire model also highlighted that spring fires in both forest types have always been larger than summer fires over the last 7000 years, such results being in agreement with present-day fire statistics. This study illustrates how fire models, built and used for forecast and firefighting today, can be used under past conditions to enhance our understanding in the fire-vegetation-climate nexus.